Effect of Deoxycholic Acid on the Performance of Liquid Electrolyte Dye-Sensitized Solar Cells Using a Perylene Monoimide Derivative - Ganesh D. Sharma; Rajnish Kurchania; Richard J. Ball; Mahesh S. Roy; John A. Mikroyannidis (International Journal of Photoenergy)
The effect of coadsorption with deoxycholic acid (DCA) on the performance of dye-sensitized solar cell based on perylene monoimide derivative (PCA) as sensitizer and liquid electrolyte had been investigated. The current-voltage characteristics under illumination and incident photon to current efficiency (IPCE) spectra of the DSSCs showed that the coadsorption of DCA with the PCA dye results in a significant improvement in short circuit photocurrent and slight increase in the open circuit photovoltage, which lead to an overall power conversion efficiency. The enhancement of short circuit current was attributed to the increased electron injection efficiency from the excited state of PCA into the conduction band of TiO2 and charge collection efficiency. The current-voltage characteristics in dark indicates a positive shift in the conduction which also supports the enhancement in the photocurrent. The coadsorption with DCA suppressed charge recombination as indicated from the electrochemical impedance spectra and thus improved the open circuit photovoltage.